1995
DOI: 10.1093/ndt/10.12.2250
|View full text |Cite
|
Sign up to set email alerts
|

Genotype distribution and transmission of hepatitis C virus (HCV) in French haemodialysed patients

Abstract: Blood transfusions and nosocomial infections were the main causes of HCV transmission in haemodialysed patients. Both screening of blood donors and aseptic measures in haemodialysis units may prevent HCV transmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 0 publications
0
5
1
Order By: Relevance
“…There are few reports regarding the distribution of HCV (sub)types in dialysis patients and all of them con cern small groups of patients [34][35][36][37], Our results are dif ferent from those of Lee et al [34], who observed a high frequency of genotype lb among HD patients in Korea. The predominance of HCV subtype lb was also observed in French HD individuals [35].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…There are few reports regarding the distribution of HCV (sub)types in dialysis patients and all of them con cern small groups of patients [34][35][36][37], Our results are dif ferent from those of Lee et al [34], who observed a high frequency of genotype lb among HD patients in Korea. The predominance of HCV subtype lb was also observed in French HD individuals [35].…”
Section: Discussioncontrasting
confidence: 99%
“…The predominance of HCV subtype lb was also observed in French HD individuals [35]. Hadiwandowo et al [36] reported the distribution of HCV genotypes in HD pa tients in China and concluded that the dominant HCV genotype was la.…”
Section: Discussionmentioning
confidence: 85%
“…In Germany, 77.6% of patients receiving HD are genotype 1 [4]. Although genotype 1a is prevalent in the general population, genotype 1b is more prevalent in patients undergoing HD in the Netherlands [11], Mexico [44], Morocco [45], and France [46]; genotype 2a in Italy [47]; genotypes 1a and 1b in Israel [48] and Indonesia [21]; and genotype 1 in Canada [49]. We may thus conclude that genotypes 1 and 2 are more prevalent in North America and Europe (60%-70%), genotype 3 is more prevalent in the Far East, Asia, and Australia, genotype 4 is more prevalent in Africa and the Middle East, genotype 5 is more prevalent in South Africa, and genotype 6 is more prevalent in Hong Kong.…”
Section: Discussionmentioning
confidence: 99%
“…Among 236 patients with HCV infection in Belarus, 127 (53.8%) and 58 (28.8%) were found with genotypes 1b and 3a, respectively (18). A study among French hemodialyzed patients reported a rate of 77% for genotype 1b (19). Subtype 1b (54%) had the highest frequency in Vienna, Austria, and surrounding areas (20).…”
Section: Discussionmentioning
confidence: 99%